Kinetics of hydroformylation of 1-octene in ionic liquid-organic biphasic media using rhodium sulfoxantphos catalyst - Deshpande, R. M.; Kelkar, Ashutosh A.; Sharma, A.; Julcour-Lebigue, C.; Delmas, Henri (Chemical Engineering Science, 2011)
Biphasic hydroformylation of 1-octene was performed using rhodium sulfoxantphos catalyst dissolved in [BuPy][BF(4)] ionic liquid. Preliminary experiments proved this system to retain the catalytic complex within the ionic liquid phase and to maintain a high selectivity towards the linear aldehyde (n:iso ratio of 30) over several cycles. Process parameter investigation showed a first order dependence of the initial rate with respect to the catalyst and 1-octene concentrations, but a more complex behavior with respect to hydrogen (fractional order) and carbon monoxide partial pressures (inhibition at high pressures). Different mathematical models were selected based on the trends observed and evaluated for data fitting. Also, rate models were derived from a proposed mechanism, using Christiansen matrix approach. To calculate concentrations of substrates in the catalytic phase as required by this kinetic modeling, solubility measurements were preformed for the gases (pressure drop technique), as well as for 1-octene and n-nonanal (thermogravimetry analysis). (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biphasic catalysis; Butylpyridinium tetrafluoroborate; kinetics; Parameter identification; Reaction engineering; solubility

Kinetics of hydrogenation of lauric acid in a batch slurry reactor using Ru-Sn/TiO2 catalyst - Shinde, S. B.; Deshpande, R. M. (Asian Journal of Chemistry, 2012)
Ru-Sn catalyst was prepared in-house by impregnation method. This catalyst was found to be stable for four recycles. The rate of hydrogenation of lauric acid (LAC) using Ru-Sn/TiO2 catalyst was found to be linearly dependent on catalyst loading, lauric acid concentration old hydrogen partial pressure. The rate data obtained from kinetic study were fitted to simple rate equation based on Langmuir-Hinshelwood (L-H) type model. Based on kinetic data the hydrogenation of lauric acid over Ru-Sn/TiO2 catalyst is proposed to occur by I dual site mechanism the activation energy for hydrogenation of lauric acid to lauryl alcohol (LAOH) using Rii-Sn/TiO2 catalyst was found to be 77.2 kJ/mol.
Keywords: Hydrogenation; kinetics; Langmuir-Hinshelwood model; Ru-Sn/TiO2 catalyst